Investigating the implementation and impact of “Better Care Better Value” prescribing policy for Angiotensin-Converting Enzyme Inhibitors and Angiotensin Receptor Blockers for treating hypertension in the UK primary care setting - Baker, Amanj (2016)
Background: In April 2009, the NHS Institute for Innovation and Improvement released four Better Care Better Value (BCBV) prescribing indicators. One indicator targeted renin–angiotensin–aldosterone system (RAAS) drugs, i.e., angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), to improve their prescribing efficiency. The indicator affects the proportion of items written for ACEIs as a percentage of the total number of prescriptions for RAAS drugs. A proportion of 80% ACEIs has been proposed and considered as an achievable target based on the small proportion (2–10%) of patients who cannot tolerate the ACEIs-related side effects, mostly dry cough. However, neither the impact of the BCBV indicator on the utilisation of ACEIs/ARBs nor its cost-saving implication is yet known. The BCBV indicator involves switching established ARBs users to ACEIs, where appropriate. However, no previous studies have specifically investigated the clinical and economic impact of the switch of ARBs and hence it is unclear whether the switch from ARBs to ACEIs, promoted by the BCBV indicator, would be associated with any clinical or economic issues. Without any financial incentives or legislation enforcement, uptake of the BCBV policy is predicted to be low, especially as evidence suggests that single measures are ineffective in altering GPs’ prescribing behaviour. However, the uptake and implementation of the BCBV indicator has not yet been explored. Aims: This thesis aimed to evaluate the impact of the BCBV indicator for ACEIs/ARBs on the utilisation of ACEIs/ARBs in treating hypertension (HT) and any associated cost savings. The effects of switching patients from ARBs to ACEIs on clinical outcomes (adherence, blood pressure [BP] level and HT-related complications), healthcare resources and costs were also investigated. Prior to this, patients’ adherence and persistence patterns (discontinuation and switching), and potential associated factors were studied. Finally, the uptake and implementation of the BCBV indicator in real practice was explored. Methods:This research used an explanatory sequential mixed-method approach. Firstly, an interrupted time series analysis was used on data extracted from the Clinical Practice Research Datalink (CPRD), from April 2006 to March 2012, to examine the impact of the BCBV indicator on the repeated cross-sectional monthly ACEIs/ARBs prescriptions and costs in patients with primary hypertension, which was validated using national dispensing datasets. Secondly, a retrospective cohort study was conducted using prescription records extracted from CPRD for patients with primary hypertension who were prescribed antihypertensive drugs from April 2006 to March 2013. Patients’ adherence and persistence patterns (including switching) to antihypertensive drug classes were quantified and their association with patients’ characteristics tested, using Generalised Linear Models and survival analysis. Thirdly, a retrospective cohort study was conducted on patients who switched their index drug class from ARBs to ACEIs to evaluate the clinical outcomes and resources used associated with ARBs switching, using data from CPRD in linkage with Hospital Episode Statistics, and applying multilevel regression for data analysis. Finally, semi-structured interviews were conducted with 16 general practitioners, to explore their views about ACEIs/ARBs prescribing and the BCBV policy to understand the reasons underpinning the effectiveness/ineffectiveness of the BCBV indicator. The interviews were recorded, transcribed verbatim and analysed using a thematic approach. Results:Impact of the BCBV indicator on ACEIs/ARBs utilisation and cost saving. The ACEIs prescription proportion declined from 71.2% in April 2006 to 70.7% in March 2012. The policy initially resulted in a sudden reduction of 0.3% (95%CI: –0.44, –0.16) in the level of ACEIs prescription proportion; however, it was thereafter associated with a sustained, significant increase of 0.013% (95%CI: 0.0007, 0.02). The failure to achieve the 80% target by the end of the study period resulted in missing a potential cost saving of 23.9% of the total ACEIs/ARBs cost. In June 2014, a potential cost saving of ~£1 million was predicted, had the 80% target been achieved; this substantial saving was several years after the availability of several low-cost generic ARBs. Adherence and persistence to antihypertensive drug classes: Among the 176,835 patients with primary hypertension included in this analysis, 38.4% and 20% were non-adherent (proportion of days covered [PDC]<80%) to their antihypertensive drug class and therapy, respectively. The discontinuation rate of antihypertensive drug class (56.1%) and therapy (35.5%) was relatively high by the end of six-year follow-up period. Using ARBs as the index drug class, prevalent hypertensive patients, prevalent antihypertensive drug users and increasing age were associated with higher PDC to antihypertensive drug class and therapy but a lower risk of drug discontinuation; whereas a higher deprivation level, comorbidity score and switching of antihypertensive drug class were associated with lower PDC to antihypertensive drug therapy but a higher risk of discontinuation. Overall, 26% of the included patients switched their antihypertensive drug class. Using ARBs, higher deprivation, higher comorbidity and prevalent antihypertensive drug users were protective factors against switching; whereas female gender, prevalent hypertensive patients, higher BP level and increasing age were associated with a higher risk of switching. Clinical and economic implications of switching patients from ARBs to ACEIs: Of the 46,193 patients who switched their antihypertensive drug therapy, only 470 patients switched from ARBs to ACEIs – they were included in this study. Based on whether the patient combined ACEIs with other antihypertensive drug classes in the post-switching period, 369 patients were classified into ACEIs-combined group and 101 patients into ACEIs-monotherapy group. Compared with the pre-switching period, the proportion of non-adherent patients (PDC<80%) in the post-switching period increased significantly (17% vs. 27%); however, this significant increase was observed only in the ACEIs-combined group (17.3% vs. 29%). The switching of ARBs was associated with a significant reduction in both systolic and diastolic BP (144.2 vs. 141.9 mmHg, p<0.001) and (84.6 vs. 82.6 mmHg, p<0.001), respectively; however, this effect was found only in the ACEIs-combined group. The incidence of all HT-related complications was comparable in both pre- and post-switching periods, except for the incidence of MI, which reduced significantly only in the ACEIs-combined group (OR=0.1, 95%CI: 0.04, 0.6). Importantly, the switching of ARBs to ACEIs was associated with a significant reduction in the total medical costs (mean cost difference: –£329.2, 95%CI: –534.6, –205.7). Uptake and implementation of the BCBV indicator: Potential barriers suggested for the poor uptake of the BCBV policy, included a lack of GP awareness of the policy, GPs’ negative attitudes toward the policy and a lack of financial incentives. Among other reasons, the current high proportion of ARBs users appeared to be related to an over-switching of ACEIs to ARBs in anticipation of an ACEIs-related dry cough. Suggested measures for increasing the policy uptake included effective dissemination strategies, linking the policy to financial incentives and providing guidance on performing the switching. Furthermore, strategies to address the over-switching of ACEIs to ARBs were considered essential for the BCBV policy to achieve its 80% ACEIs target. Conclusions:The BCBV indicator was ineffective and failed to achieve the 80% ACEIs target. The association of achieving the 80% target with a remarkable cost-saving opportunity and the lack of any negative clinical consequences following the switching of ARBs to ACEIs indicate the ongoing necessity to reconsider and reinforce this policy through multiple initiatives to increase its future effectiveness, building on the study’s identified barriers and suggested solutions. This thesis represents a case study of a failed and an ineffective prescribing policy, attributed primarily to inappropriate policy implementation. It provides key lessons for policy makers and healthcare authorities on the importance of effective implementation strategies as an integral component to any successful policy.